Nanotechnology: The new perspective in precision agriculture - Duhan, Joginder Singh; Kumar, Ravinder; Kumar, Naresh; Kaur, Pawan; Nehra, Kiran; Duhan, Surekha (Biotechnology reports (Amsterdam, Netherlands), 2017)
•Precision farming is measuring and responding to inter and intra-field variability in crops to form a decision support system.•About 40–70% of N, 80–90% of P and 50–70% of K of the applied fertilizers is lost to the environment causing pollution.•Nanofertilizers helps in slow and sustained release of agrochemicals resulting in precise dosage to the plants.•Green synthesized Ag, ZnO and TiO2 NPs are extensively used for plant protection and treatment of diseases.•Biosensors helps in detecting pesticides in the vegetable crops and form a decision support system for crop commodities. Nanotechnology is an interdisciplinary research field. In recent past efforts have been made to improve agricultural yield through exhaustive research in nanotechnology. The green revolution resulted in blind usage of pesticides and chemical fertilizers which caused loss of soil biodiversity and developed resistance against pathogens and pests as well. Nanoparticle-mediated material delivery to plants and advanced biosensors for precision farming are possible only by nanoparticles or nanochips. Nanoencapsulated conventional fertilizers, pesticides and herbicides helps in slow and sustained release of nutrients and agrochemicals resulting in precise dosage to the plants. Nanotechnology based plant viral disease detection kits are also becoming popular and are useful in speedy and early detection of viral diseases. In this article, the potential uses and benefits of nanotechnology in precision agriculture are discussed. The modern nanotechnology based tools and techniques have the potential to address the various problems of conventional agriculture and can revolutionize this sector.